NMR quantification of lactate production and efflux and glutamate fractional enrichment in living human prostate biopsies cultured with [1, 6‐13C2]glucose. Issue 2 (28th March 2019) - Bancroft Brown, Jeremy; Sriram, Renuka; VanCriekinge, Mark; Delos Santos, Romelyn; Sun, Jinny; Delos Santos, Justin; Tabatabai, Z. Laura; Shinohara, Katsuto; Nguyen, Hao; Peehl, Donna M.; Kurhanewicz, John
Abstract : Purpose: Image‐guided prostate biopsies are routinely acquired in the diagnosis and treatment monitoring of prostate cancer, yielding useful tissue for identifying metabolic biomarkers and therapeutic targets. We developed an optimized biopsy tissue culture protocol in combination with [1, 6‐ 13 C2 ]glucose labeling and quantitative high‐resolution NMR to measure glycolysis and tricarboxcylic acid (TCA) cycle activity in freshly acquired living human prostate biopsies. Methods: We acquired 34 MRI‐ultrasound fusion‐guided prostate biopsies in vials on ice from 22 previously untreated patients. Within 15 min, biopsies were transferred to rotary tissue culture in 37°C prostate medium containing [1, 6‐ 13 C2 ]glucose. Following 24 h of culture, tissue lactate and glutamate pool sizes and fractional enrichments were quantified using quantitative 1 H high resolution magic angle spinning Carr‐Purcell‐Meiboom‐Gill (CPMG) spectroscopy at 1°C with and without 13 C decoupling. Lactate effluxed from the biopsy tissue was quantified in the culture medium using quantitative solution‐state high‐resolution NMR. Results: Lactate concentration in low‐grade cancer (1.15 ± 0.78 nmol/mg) and benign (0.74 ± 0.15 nmol/mg) biopsies agreed with prior published measurements of snap‐frozen biopsies. There was substantial fractional enrichment of [3‐ 13 C]lactate (≈70%) and [4‐ 13 C]glutamate (≈24%) in both low‐grade cancer and benign biopsies. Although a significant difference in tissue [3‐ 13 C]lactate fractional enrichment was not observed, lactate efflux was significantly higher ( P < 0.05) in low‐grade cancer biopsies (0.55 ± 0.14 nmol/min/mg) versus benign biopsies (0.31 ± 0.04 nmol/min/mg). Conclusion: A protocol was developed for quantification of lactate production–efflux and TCA cycle activity in single living human prostate biopsies, allowing metabolic labeling on a wide spectrum of human tissues (e.g., metastatic, post‐non‐surgical therapy) from patients not receiving surgery.